Does e-participation Influence and Improve Political Decision Making Processes? Evidence From a Local Government (Lex localis - Journal of Local Self-Government, 2016)
In Local Governments, the quality of representative democracy is also measured by the extent to which demands of citizens and groups influence the agendas of local politicians. In this context, the potential of Internet and the NIT as tools that encourage participation, exchange and deliberation, have not been fully explored by either the local elites or the citizens to foster the discursive and decision-making dimensions of local democracy. But despite the growing importance of e-participation in improving local democracy, it remains unclear to what extent it also contributes to the introduction of new repertoires of action to improve efficiency and quality of local public service provision and, therefore, involving citizens meaningfully in the decision-making process continues to be a challenge. With this in mind and using recent empirical evidence from the current development of e-participation to improve administrative performance in a large city government, intended to enhance not only local democracy but also better decision-making, the paper focus on this gap on research by exploring to what extent e-participation contributes to foster, influence and improve local decision-making.